PATRONAGE OF ISLAMIC AND CONVENTIONAL BANKS: THE CASE OF SYRIA - Aldeen, Khaled Nour; Ali Shah, Syed Alamdar; Herianingrum, Sri (Universitas Negeri Surabaya, 2019)
The aim of this study is to understand perception of conventional banks’ customers towards Islamic banking by examining their level of awareness about Islamic banking. The qualitative approach was used in the form of semi-structured interviews under the phenomenological approach in Damascus city. The main findings of this research are customers lack awareness of Islamic banking operations. Furthermore, Islamic banks’ stuff play a crucial rule to enhance awareness and willingness towards their services. This study revealed that an informative advertising campaign is highly recommended to raise the awareness level among Syrians towards Islamic banking. Moreover, Islamic banks should be more selective especially when they recruit customer service operation staff. This research is a pioneering attempt towards Islamic banking issues in the case of Syria from a customer perspective. It contributes to the Syrian perceptions towards Islamic banking literature.